Clinical evaluation of the therapeutic effects of atelocollagen absorbable punctal plugs - Kadonosono K; Uchio E; Takano Y; Hirai K (Clinical Ophthalmology, 2012)
Kaori Hirai1,4, Yoji Takano2, Eiichi Uchio3, Kazuaki Kadonosono41Department of Ophthalmology, International Goodwill Hospital, 2Department of Ophthalmology, Kitasato Institute Hospital, 3Department of Ophthalmology, Fukuoka, Fukuoka, Japan; 4Department of Ophthalmology, Yokohama City University Medical Center, Yokohama, JapanPurpose: To evaluate the therapeutic effects of atelocollagen absorbable punctal plugs.Method: Seventy-four eyes in 37 patients with dry eye disease (DED) underwent punctal plug occlusion using atelocollagen plugs and were followed up for 24 weeks. Subjective symptoms were evaluated using the ocular surface disease index (OSDI) questionnaire. Ocular surface disease parameters, including the Schirmer test, phenol red thread test, tear break-up time (TBUT), and fluorescein and Rose Bengal staining, were recorded before and 1, 4, 8, 16, and 24 weeks after treatment.Results: In comparison with the pretreatment data, the subjective symptoms and ocular surface disease parameters showed significant improvement after atelocollagen punctal occlusion. The average time of relapse was 17.4 ± 5.1 weeks. No severe complications occurred, and none of the plugs had to be removed because of local discomfort or epiphora.Conclusion: Atelocollagen absorbable punctal plugs effectively improved ocular surface disorders in DED. These plugs are a safe and effective alternative in the treatment of DED.Keywords: atelocollagen, absorbable punctual plug, dry eye